Use of demonstrations and experiments in teaching business statistics. Issue 2 (2003) - Johnson, D. G.; John, J. A.
Abstract : The aim of a business statistics course should be to help students think statistically and to interpret and understand data, rather than to focus on mathematical detail and computation. To achieve this students must be thoroughly involved in the learning process, and encouraged to discover for themselves the meaning, importance and relevance of statistical concepts. In this paper we advocate the use of experiments and demonstrations as aids to achieving these goals. A number of demonstrations are given which can be used to illustrate and explain some key statistical ideas.